La crisis del empleo de los jóvenes : ¡Actuemos ya!. - Office, International Labour (Conferencia Internacional del Trabajo 101.ª reunión 2012, Informe V., 2012)
Report submitted to the delegates of the 101st International Labour Labour Conference for general discussion.